The Effect of Venture Capital on the Growth of Startups in Indonesia: A Case Study on BRI Ventures - Chairanisa Natasha Miraza; Elvia R Shauki (Universitas Hayam Wuruk Perbanas, 2022)
The low success rate of startups has caused venture capital firms to bear a large risk of investment failure (BRI Ventures, 2021). Venture capital firms play an important role in identifying potential startups and being the driving force for startup success. This study aims to find out the role of BRI Ventures (BVI) in increasing the success rate of startups in Indonesia, how BRI Ventures (BVI) makes funding decisions, and the criteria set before funding startups. The data analysis uses descriptive qualitative analysis, which includes content, thematic, and constant comparative analysis and is processed using the NVivo 12 Pro software application. This study uses the diffusion of innovation theory to examine the role of BRI Ventures (BVI) in increasing the success rate of startups in Indonesia. The results show that BRI Ventures (BVI) uses the 5Ps approach, a self-designed investment analysis tool to assess whether a startup is feasible to fund. The indicators of 5Ps include people, product, potential market, performance, and potential upsides. The people indicator, which consists of the founder and the team, plays an important role in the success of a startup. The findings of this study suggest that BRI Ventures proactively provide innovations through mentoring programs to increase the success rate of startups. This research is expected to be useful in the financial sector, especially in terms of funding and innovation, for the business sustainability.